Monte Carlo Simulation to relate primary and ﬁnal fragments mass and kinetic energy distribution from low energy ﬁssion of U-234 - Montoya, Modesto (2008)
The kinetic energy distribution as a function of mass of ﬁnal fragments (m) from low energy ﬁssion of U-234, measured with the Lohengrin spectrometer by Belhafaf et al., presents a peak around m = 109 and another around m = 122. The authors attribute the ﬁrst peak to the evaporation of a large number of neutrons around the corresponding mass number; and the second peak to the distribution of the primary fragment kinetic energy. Nevertheless, the theoretical calculations related to primary distribution made by Faust et al. do not result in a peak around m = 122. In order to clarify this apparent controversy, we have made a numerical experiment in which the masses and the kinetic energy of ﬁnal fragments are calculated, assuming an initial distribution of the kinetic energy without peaks on the standard deviation as function of fragment mass. As a result we obtain a pronounced peak on the standard deviation of the kinetic energy distribution around m = 109, a depletion from m = 121 to m = 129, and an small peak around m = 122, which is not as big as the measured by Belhafaf et al. Our simulation also reproduces the experimental results on the yield of the ﬁnal mass, the average number of emitted neutrons as a function of the provisional mass (calculated from the values of the ﬁnal kinetic energy of the complementary fragments) and the average value of fragment kinetic energy as a function of the ﬁnal mass.